New guidelines for weight gain during pregnancy: what obstetrician/gynecologists should know - Rasmussen, Kathleen M. (2009)
PURPOSE: To review the recently issued guidelines for weight gain during pregnancy. RECENT FINDINGS: These guidelines were developed to minimize the negative health consequences for both mother and fetus of inadequate or excessive gain. They call for categorizing women’s prepregnancy body mass index using the WHO/NHLBI cutoff points and provide ranges of recommended weight gain for underweight (28–40 lb), normal-weight (25–35 lb), overweight (15–25 lb) and obese (11–20 lb) gravidas. Data were insufficient to construct specific guidelines for women with class II or class III obesity. Women should attempt to conceive at a normal weight for better obstetric outcomes. Improved comprehensive preconceptional care is necessary to help women reach this goal. Most American women currently gain below or above the new ranges, so changes are required in both women’s behavior and how their care is managed. Data from a variety of interventions related to improved diet and increased physical activity show that individualized care can assist women in gaining within these guidelines. SUMMARY: The guidelines offer many opportunities for obstetrician/gynecologists, together with ancillary health care providers, to assume a larger role as “women’s health care physicians” and to conduct research that could improve the health of mothers and children.